Audit Komunikasi Media Sosial Instagram Kementerian PUPR @KEMENPUPR - Nurimansyah, Rafi; Ulhaq Bintoro, Muhammad Dafa; Ihsan At-Thariq, Muhammad; Rachmawati, Farikha (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The Ministry of Public Employment and People's Housing (Kemen PUPR) won the award in the category of "Best Social Media Management" Tempo Media Award 2022 and "Gold Winner Sub Category Social Media" in the 2022 Public Relations Indonesia Award. The research focuses mainly on auditing public communications through Kemen PUPR's Instagram @kemenpupr social media account. The research uses a qualitative method with a communication audit approach and is implicated in Goutama's Social Media audit instrument. The design of the research uses the six main stages of the Nothwest Npower approach. The results of the audit of social media communications on Instagram @kemenpupr of the Ministry of PUPR based on the analysis of the performance and capacity of the organization have been performed optimally. The aspects of strategy, implementation, integration, and support show that there is regularity, integrity, and collaboration that the PUPR Ministry does in communicating with the public. Nevertheless, there are shortcomings in the integration aspect because there are no biolink links to Facebook, Twitter, and YouTube. While the maturity level also reached the optimized level, the evaluated level of Instagram @kemenpupr has not been audited since 2021.